Modeling transverse mode instability experiment using the phase-matched model - Young, Joshua T.; Hu, Zhihao; Menyuk, Curtis; Hu, Jonathan (Optica, 2024)
We compare the results of experiment and phase-matched model for transverse mode instability (TMI). The simulation accurately identifies the threshold of TMI, which shows strong potential for future design optimizations.
Specialty Optical Fibers 2024, Québec City Canada, 28 July–1 August 2024
Keywords: Laser amplifiers; Fiber lasers; High speed photography; UMBC Optical Fiber Communications Laboratory; UMBC High Performance Computing Facility (HPCF); Nonlinear effects; Refractive index; Optical amplifiers; UMBC Computational Photonics Lab